Elevated Serum Mannose Levels as a Marker of Polycystic Ovary Syndrome - Feng, Di; Shi, Bei; Bi, Fangfang; Sagnelli, Matthew; Sun, Xiaoli; Jiao, Jiao; Wang, Xiuxia; Li, Da (Frontiers in Endocrinology, 2019)
Background: Recent reports have highlighted the role of monosaccharide biosynthesis in the pathogenesis of polycystic ovary syndrome (PCOS), suggesting that these processes may serve as a biomarker in PCOS. Mannose is the main monosaccharide for protein glycosylation in mammals; however, the correlation between mannose and PCOS remains largely unknown. Materials and methods: A total of 132 Chinese Han women were recruited at Shengjing Hospital of China Medical University. Mannose levels were measured in serum samples collected from 71 patients with PCOS (29 lean, 42 obese) and 61 control subjects (28 lean, 33 obese). Receiver operating characteristics (ROC) curves were prepared to compare the diagnostic performance of mannose and hormonal parameters, individually or in combination. Multivariate logistic regression analysis was used to assess whether serum mannose levels were associated with PCOS after adjusting for other co-variables Results: We showed that serum mannose levels were significantly increased in PCOS patients compared with control subjects regardless of obese status, and hyperandrogenic PCOS patients had higher serum mannose levels than normo-androgenic PCOS and control subjects. In addition, serum mannose levels were significantly correlated with serum androgen levels. Mannose had an area under the curve (AUC) of 73% at a cutoff value of 225.79 ng/mL with a sensitivity of 66.2% and specificity of 73.8% for predicting PCOS. There were no differences between mannose, total testosterone, free testosterone, or dehydroepiandrosterone sulfate in the reliability of predicting PCOS using the method outlined by Hanley and McNeil. Combining mannose and total testosterone resulted in a higher AUC of 83.3%, and had moderate sensitivity (78.9%) and specificity (77%) for predicting PCOS. The positive and negative predictive values were 80% and 75.8%, respectively. Multivariate logistic regression revealed that higher serum mannose levels were strongly associated with an increased risk of PCOS (P = 0.016; odds ratio, 5.623; 95% confidence interval, 1.371 23.070). Conclusion: Taken together, substantially elevated serum mannose levels are significantly associated with PCOS, highlighting the importance of further research into the role of mannose in the pathogenesis of PCOS.